2020
DOI: 10.21203/rs.3.rs-46139/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel surgical approach and technique and short-term clinical efficacy for the treatment of proximal humerus fractures with the combined use of medial anatomical locking plate fixation and minimally invasive lateral locking plate fixation

Abstract: Background and hypothesis: The typical anterolateral approach is widely used to treat proximal humerus fractures with lateral locking fixation. However, lateral fixation cannot completely avoid medial reduction loss and varus deformity especially in the cases of an unstable medial column. We present a novel medial surgical approach and technique together with a minimally invasive lateral locking plate to fix proximal humerus fractures with an unstable medial column.Materials and Methods: An anatomical study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced the screw cutting, varus deformity, and the probability of secondary surgery. Various methods are used to compensate for the effect of the medial support screw and strengthen medial support in clinical practice, such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate [7][8][9][10][11]. The selection, treatment, and placement of fibula grafts and titanium mesh require high technical experience among orthopedic doctors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced the screw cutting, varus deformity, and the probability of secondary surgery. Various methods are used to compensate for the effect of the medial support screw and strengthen medial support in clinical practice, such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate [7][8][9][10][11]. The selection, treatment, and placement of fibula grafts and titanium mesh require high technical experience among orthopedic doctors.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods for strengthening medial support in clinical practice, such as allograft fibula implantation [7], titanium mesh implantation [8], bone cement [9], and auxiliary support plates [10][11]. In clinical practice, the authors have used a 1/3 tubular steel plate as an auxiliary plate to develop the shape according to the lateral anatomical structure of the internodal sulcus, placing it on the outside of the internodal sulcus.…”
mentioning
confidence: 99%
“…A comparative study by Shen et al [17] reported that placement of the medial support screw greatly reduced screw cutting, varus deformity, and the probability of a secondary surgery. In clinical practice, various methods such as autologous or allogeneic fibula implantation, titanium mesh implantation, and the use of an auxiliary steel plate are used to compensate for the effect of the medial support screw and strengthen medial support [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, several methods, such as allograft fibula implantation [7], titanium mesh implantation [8], bone cement [9], and auxiliary support plates [10][11], are used for strengthening the medial support. Authors have used a 1/3 tubular steel plate as an auxiliary plate to develop a shape according to the lateral anatomical structure of the internodal sulcus, placing the plate on the exterior of the internodal sulcus.…”
Section: Introductionmentioning
confidence: 99%
“…The total effective rate was calculated as follows: Total effective rate = (significant effect + effective)/ total number of columns *100%. [2] We compared the clinical indicators of patients in the two groups, including dressing change times, wound healing time, blood loss during operation time, quality of life score and pain score, etc. The higher the quality of life score, the better the patient's quality of life.…”
Section: Observation Criteriamentioning
confidence: 99%